MANAJEMEN ORGANISASI SISWA INTRA SEKOLAH DALAM MENINGKATKAN KARAKTER KEMANDIRIAN SISWA STUDI MULTISITUS DI SMAN 1 TANJUNGANOM NGANJUK DAN SMKN 2 KOTA KEDIRI - Naila Nuril Fauziah; Arina Sabila Qak (STKIP Pesisir Selatan, 2026)
Objective: This study was conducted to analyze the planning, implementation, and evaluation of Student Council (OSIS) management in fostering independence. Data were collected through observation, interviews, and documentation. Data analysis was performed through data reduction, data display, and data verification. The results of the study indicate that: (1) At SMAN 1 Tanjunganom Nganjuk, OSIS management planning is carried out using a rational, flexible, coordinated, efficient, and effective approach. Meanwhile, OSIS management planning at SMKN 2 Kota Kediri is also strategic and student-needs-based, carried out by considering indicators of rationality, flexibility, coordination, efficiency, and effectiveness. (2) The implementation of OSIS management at SMAN 1 Tanjunganom Nganjuk and SMKN 2 Kota Kediri indicates that OSIS executives not only execute programs but also adhere to several indicators, namely: providing motivation, effective leadership, communication among individuals and groups, making sound decisions, and implementing work plans. (3) The evaluation of OSIS management at SMAN 1 Tanjunganom Nganjuk is conducted periodically and comprehensively using clear benchmarks, a structured data collection system, in-depth goal analysis, constructive feedback, and concrete follow-up actions. Meanwhile, at SMKN 2 Kota Kediri, this evaluation is supported by systematic and continuous data collection through comprehensive and in-depth activity reports.